RELATIONSHIP BETWEEN WORKER'S CHARACTERISTIC AND WORK ENVIRONMENT ON ACCIDENT OCCURRENCE IN PT WASKITA KARYA (PERSERO) - Rindang Rifqi Akmalia; Erwin Dyah Nawawinetu (Journal of Industrial Hygiene and Occupational Health, 2018)
Background: Workplace accidents are accidents related to company activities that may occur during work and on the way to or from work. Occupational accidents occur are influenced by several factors namely the characteristics of workers, work environment and management. Purpose: This study was analyze the description of the relationship between worker's characteristic factors and work environment on accident occurrence in PT Waskita Karya (Persero) Tbk KLBM Toll Project Zone 2 in Bunder Reservoir area on iron fabrication section. Methods: This was an observational descriptive research with cross sectional approach. The number of respondents were 54 respondents spread in seven areas. The collected data analyzed by using frequency distribution and continued by contingency coefficient test (C) to find out how strong the relationship between the two variables. Result: The results showed that respondents who have experienced the incidence of occupational accidents were 25 respondents (46.3%). Of the five variables studied, the description of the age relationship, level of knowledge, and compliance work instructions with the incidence of work accidents were quite strong and strong with the value of C respectively for 0.434, 0.434 and 0.509. While the picture of attitude and housekeeping relationship with the incidence of work accident was very weak. Conclusion: In conclusion, it was summarized that the younger the respondent’s age, the less the respondent’s knowledge and the less respondents obedience over the work instruction will affect to the higher frequency of accidents. It is recommended that the company promote the safety briefing program before starting work and provide training especially for young respondents and those with less knowledge.Keyword: Work Accident, Age, Knowledge, Attitude, Work Instruction Compliance, Housekeeping.